Marketing - McMurtry, Jeanette; Hiam, Alexander (For dummies, 2017)
The classic, bestselling marketing guide, updated for the digital era Marketing For Dummies, 5 th Edition is the ultimate handbook for boosting your business. Whether you're a small mom-and-pop shop, a local nonprofit, or a mid-size business looking to grow, the right marketing approach can make your company or organization stand out from the crowd. This book shows you how to find, reach, and engage with your customers in a way that brings in business. This new  edition, updated to align with the latest marketing revolution, introduces you to essential techniques including search engine, guerilla, global, and behavior marketing. You'll learn where to find your people, and how to give them what they want—how they want it—using behavioral techniques. You'll discover inexpensive online marketing and promotion tools, proving that budget doesn't have to be an insurmountable obstacle. You'll find up-to-date marketing plans, resources, and examples throughout to help you get out there and get your business noticed today! Today's marketing treats every aspect of customer interaction—including customer service and the product itself—as an opportunity to grow. This book shows you how to harness the power of these techniques to drive traffic, boost sales, and move your business forward. Turn web visibility into real-world traffic and sales Reach the right people at the right time Develop a cohesive marketing plan for any budget Source locally, market dynamically, and connect with your community Whether you're looking for fundamental marketing skills, seeking guidance on social media and analytics, or need a full-blown comprehensive web marketing strategy, this book has you covered. Marketing For Dummies, 5 th Edition helps you open the door to a new, more successful phase of business.
Keywords: Marketing : Management; Marketing